Reading the Right to Food into the African Charter on Human and Peoples’ Rights - Mbazira, Christopher (Economic and Social Rights in South Africa, 2004)
Reading the right to food into the African Charter on Human and Peoples' Rights Christopher Mbazira The African Charter on Human and Peoples' Rights (the Charter) of 1981 is the principal regional instrument protecting human and peoples' rights in Africa. It incorporates a wide range of socio-economic rights, including the rights to property, to work under favourable conditions and equal pay for equal work, to health, to education, family rights and the right to self-determination. However, the Charter does not expressly recognise the right to food.